Work-life Balance dan Stress Kerja: Tinjauan Literatur Sistematis - Yusuf Murtadlo Hidayat; Syamsul Hadi Senen; Rofi Rofaida (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2022)
The purpose of this study is to provide a literature review on work-life balance and work stress. A total of 125 articles were selected from 140 found from the Google Scholar database for the years 2016 – 2021. The articles found were classified by all authors, year of publication, publisher journal name, and citing. Overall, from year to year, research on the concept of work-life balance that is tied to stress tends to increase. In the last 2 years, this topic has been widely discussed again regarding the Covid-19 pandemic.